2016
DOI: 10.5664/jcsm.6124
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Fragmentation Does Not Explain Misperception of Latency or Total Sleep Time

Abstract: Study Objectives: Perception of sleep-wake times may differ from objective measures, although the mechanisms remain elusive. Quantifying the misperception phenotype involves two operational challenges: defining objective sleep latency and treating sleep latency and total sleep time as independent factors. We evaluated a novel approach to address these challenges and test the hypothesis that sleep fragmentation underlies misperception. Methods: We performed a retrospective analysis on patients with or without o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 45 publications
1
17
2
Order By: Relevance
“…Despite extensive work investigating the basis of misperception, the causes remain the subject of discussion. 36 , 39 , 63 We found that misperception of TST was associated with HR dipping, which runs counter to the prediction that dipping should reflect better sleep quality. TST misperception was only related to HRV frequency metrics derived from stage N1 and, in a manner that suggests more stable cardiac function, was related to greater misperception, which does not support the hypothesis that sympathetic tone contributes to the under-estimation of sleep.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Despite extensive work investigating the basis of misperception, the causes remain the subject of discussion. 36 , 39 , 63 We found that misperception of TST was associated with HR dipping, which runs counter to the prediction that dipping should reflect better sleep quality. TST misperception was only related to HRV frequency metrics derived from stage N1 and, in a manner that suggests more stable cardiac function, was related to greater misperception, which does not support the hypothesis that sympathetic tone contributes to the under-estimation of sleep.…”
Section: Discussioncontrasting
confidence: 93%
“…However, we previously reported a similarly unexpected finding that misperception was associated with more stable sleep (fewer transitions) based on standard stage scoring. 39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some degree of mismatch between the subjective experience and objective measurements of sleep is more common, 8 although the mechanisms remain uncertain. 18 In fact, selfreporting of sleep-wake times is influenced by many factors, including how the question is asked. 19 In a clinical field that is still defined entirely by the subjective experience, misperception among insomnia patients has until recently been considered little more than an academic curiosity.…”
Section: Clinical History and Subtypes Of Chronic Insomniamentioning
confidence: 99%
“…6 They performed a retrospective analysis on 643 patients who had PSG performed in their lab. The morning after their sleep study, all subjects were asked to estimate their total sleep time (TST).…”
mentioning
confidence: 99%